2017
DOI: 10.1103/physrevb.95.104432
|View full text |Cite
|
Sign up to set email alerts
|

Thermal spin torques in magnetic insulators

Abstract: The damping of spin waves transmitted through a two-port magnonic device implemented on a yttrium iron garnet thin film is shown to be proportional to the temperature gradient imposed on the device. The sign of the damping depends on the relative orientation of the magnetic field, the wave vector, and the temperature gradient. The observations are accounted for qualitatively and quantitatively by using an extension of the variational principle that leads to the Landau-Lifshitz equation. All parameters of the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 28 publications
1
14
0
Order By: Relevance
“…Then, this measurement avoids SSE 19,[40][41][42] and allows a precise determination of the temperature gradient since it is inplane, e.g., by using a thermal camera. 43,44 Previous experiments observed an enhancement of the ANE in stacks containing heavy elements, indicating the relevance of strong spin orbit coupling (SOC) to obtain large Nernst coefficients N ANE , 20,45 e.g., Uchida et al showed that the anomalous Nernst coefficients change from about 0.1 lV/K to 1 lV/K by introducing strong SOC. In this work, we observed an ANE in Ta/IrMn/CoFeB/MgO/Ta structures that is almost 50 times larger than that of a thin film of Ta/ CoFeB/MgO/Ta, i.e., without the IrMn layer.…”
mentioning
confidence: 99%
“…Then, this measurement avoids SSE 19,[40][41][42] and allows a precise determination of the temperature gradient since it is inplane, e.g., by using a thermal camera. 43,44 Previous experiments observed an enhancement of the ANE in stacks containing heavy elements, indicating the relevance of strong spin orbit coupling (SOC) to obtain large Nernst coefficients N ANE , 20,45 e.g., Uchida et al showed that the anomalous Nernst coefficients change from about 0.1 lV/K to 1 lV/K by introducing strong SOC. In this work, we observed an ANE in Ta/IrMn/CoFeB/MgO/Ta structures that is almost 50 times larger than that of a thin film of Ta/ CoFeB/MgO/Ta, i.e., without the IrMn layer.…”
mentioning
confidence: 99%
“…Considering the temperature-dependent resonance frequencies reported in ref. 48 , we estimate a temperature increase of~6 K. The wavevectors of the magnons were defined by the geometric design in conventional nonmagnetic CPWs as reported earlier, but were modified when mCPWs were used. In mCPW2, the microwave currents induced by the propagated magnons were probed via a coaxial cable by a port of the VNA, and corresponding scattering parameters were analyzed.…”
Section: Methodsmentioning
confidence: 99%
“…The notation is to be understood as, e.g., . One consequence of this extra term in the generalized force is a damping term in the Landau–Lifshitz equation which is proportional to the temperature gradient [ 35 ]. The force term is the equivalent for a continuum description to the force that a magnetic dipole experiences in a non-uniform magnetic induction field (Stern–Gerlach experiment).…”
Section: Thermodynamics With Magnetic Dipoles and Fieldsmentioning
confidence: 99%